K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

16 tháng 12 2024

36,2 x 101 - 36 - 0,2

= 36,2 x 101 - 36,2

= 36,2 x (101 - 1)

= 36,2 x 100

= 3620

R
16 tháng 12 2024

35,04 : 4 - 6,87 = 8,76 - 6,87

                         = 1,89.

16 tháng 12 2024

35,04:4-6,87=8,76-6,87

                    = 1,89

16 tháng 12 2024

 2cm2 50mm2 = 200mm2 50mm2 = 250mm2

Vậy 2cm2 50mm2 = 250mm2

 

 

16 tháng 12 2024

`2 cm^2 50 mm^2 = 200 mm^2 + 50 mm^2 = 250 mm^2`

16 tháng 12 2024

m x 3 + m x 7 = 1530

m x (3 + 7)     = 1530

m x 10            = 1530

m                    = 1530 : 10

m                    = 153

Vậy m = 153

16 tháng 12 2024

153

16 tháng 12 2024

728:21 dư ?

giúp m với

16 tháng 12 2024

a; 3,2 : 0,5 + 3,2 : 0,125

= 3,2 x 2 + 3,2 x 8

= 3,2 x (2 + 8)

= 3,2 x 10

= 320

 

16 tháng 12 2024

\(Ta\) \(có:\)

\(30=2\cdot3\cdot5\)

\(42=2\cdot3\cdot7\)

\(Do\) \(đó:\) \(ƯCLN\left(30,42\right)=2\cdot3=6\)

\(Suy\) \(ra:\) \(ƯC\left(30,42\right)=Ư\left(6\right)=\left\{1;2;3;6\right\}\)

Vậy \(ƯC\left(30,42\right)=\left\{1;2;3;6\right\}\)

 

16 tháng 12 2024

Các ước chung của 30 và 42 là: -6; -3; -2; -1; 1; 2; 3; 6.

16 tháng 12 2024

\(8^7.\left(-8\right)^5=-8^7.8^5=-8^{7+5}=-8^{12}\)

16 tháng 12 2024

\(\sqrt{x-2}\) + \(\dfrac{1}{3}\) = 1 (đk \(x\ge\) 2)

\(\sqrt{x-2}\) + \(\dfrac{1}{3}\) = 1

      \(\sqrt{x-2}\)   = 1 - \(\dfrac{1}{3}\)

       \(\sqrt{x-2}\) = \(\dfrac{2}{3}\)

       \(x-2\)  = (\(\dfrac{2}{3}\))2

       \(x-2\) = \(\dfrac{4}{9}\)

       \(x=\dfrac{4}{9}\) + 2

       \(x=\dfrac{22}{9}\)

Vậy \(x=\dfrac{22}{9}\) 

         

 

16 tháng 12 2024

\(\sqrt{x-2}\) = \(\dfrac{2}{3}\) (đk \(x-2\) ≥ 0; \(x\ge\) 2)

  \(x-2\) =(\(\dfrac{2}{3}\))2

 \(x-2\) = \(\dfrac{4}{9}\)

 \(x=\dfrac{4}{9}\) + 2

 \(x=\dfrac{22}{9}\)

Vậy \(x=\dfrac{22}{9}\)

 

  

16 tháng 12 2024

ĐKXĐ: \(x\ge2\)

\(\sqrt{x-2}=\dfrac{2}{3}\)

\(x-2=\dfrac{4}{9}\)

\(x=\dfrac{4}{9}+2\)

\(x=\dfrac{22}{9}\) (nhận)

Vậy \(x=\dfrac{22}{9}\)

16 tháng 12 2024

|\(x\)| - 2,2 = 1,3

|\(x\)| = 1,3  + 2,2

|\(x\)| = 3,5

\(\left[{}\begin{matrix}x=-3,5\\x=3,5\end{matrix}\right.\)

Vậy \(x\in\) {-3,5; 3,5} 

16 tháng 12 2024

\(\left|x\right|-2,2=1,3\)

\(\left|x\right|=1,3+2,2\)

\(\left|x\right|=3,5\)

\(x=-3,5\)\(x=3,5\)